2009
DOI: 10.1177/1077558709331812
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hospital Organizational Culture to Patient Safety Climate in the Veterans Health Administration

Abstract: Improving safety climate could enhance patient safety, yet little evidence exists regarding the relationship between hospital characteristics and safety climate. This study assessed the relationship between hospitals' organizational culture and safety climate in Veterans Health Administration (VA) hospitals nationally. Data were collected from a sample of employees in a stratified random sample of 30 VA hospitals over a 6-month period (response rate = 50%; n = 4,625). The Patient Safety Climate in Healthcare O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 65 publications
(84 reference statements)
9
93
0
8
Order By: Relevance
“…137,143 Our findings broadly support existing research that shows a more positive assessment of safety climate by managers than by clinical staff. 37,102,103,229,230 The teamwork climate 25 results, but not other components of the survey-based safety climate measure, accord with other studies that found nurses' assessments of aspects of safety climate more negative than doctors' assessments. 106,218,228 To what extent might the empirical results be considered predictable?…”
Section: Comparison Correlation Agreementsupporting
confidence: 77%
See 1 more Smart Citation
“…137,143 Our findings broadly support existing research that shows a more positive assessment of safety climate by managers than by clinical staff. 37,102,103,229,230 The teamwork climate 25 results, but not other components of the survey-based safety climate measure, accord with other studies that found nurses' assessments of aspects of safety climate more negative than doctors' assessments. 106,218,228 To what extent might the empirical results be considered predictable?…”
Section: Comparison Correlation Agreementsupporting
confidence: 77%
“…More specifically, studies of organisational culture suggest that contrasting cultures support different aspects of safety: although bureaucratic hierarchies are comfortable with predictability such as that which comes from reliance on evidence-based rules of care, more entrepreneurial and/or group-based cultures may be more strongly associated with a safety climate. 59,103 Fifth, the scope and limitations of each method may reduce the degree to which they can be said to be looking at the same aspects of safety culture and climate. Table 44 illustrates this, using the framework proposed by Vincent and collegues 56 for analysing risk and safety in clinical medicine.…”
Section: Comparison Correlation Agreementmentioning
confidence: 99%
“…Culturas construtivas, com enfoque interno mais voltado para a flexibilidade e a liberdade (cultura clã) e foco externo mais voltado para a diferenciação (cultura inovadora), promovem um bom clima organizacional que se materializa em atitudes positivas no ambiente de trabalho (GERSHON et al, 2004;GLISSON;GREEN, 2006;AARONS;SAWITZKY, 2006;HARTMANN et al, 2009). Por sua vez, a cultura hierárquica esteve associada na pesquisa de Hartmann et al (2009) Diante desses achados, pode-se dizer que a Clínica São Pedro apresenta aspectos de uma cultura organizacional construtiva e de bom clima organizacional, que contribuirão para uma prestação de serviços de maior qualidade junto aos pacientes, pela geração de comportamentos positivos dos colaboradores relativos ao comprometimento e eficiência na realização das tarefas, assim como para a retenção dos talentos da empresa.…”
Section: Discussão Dos Resultadosunclassified
“…Safety culture has to do with the concrete values that guide organizational behaviors across multiple domains of the larger organization (Hartmann, et al , 2009;Maierhofer, Griffin, & Sheehan, 2000). The management practices observation classification system can also be used throughout the study period in the identification and monitoring of fundamental social exchange based management practices associated with knowledge transfer capacities to predict prog ram sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…Laing et al (2005) suggests that improvements in communication practices and strategies are required prior to observing improvements in individual perceptions about the organization and subsequent behavior changes. It has been observed in the literature that some of the main challenges and barriers encountered in PE have to do with lack of effective organizational communication between levels of management and the front line level (Hartmann et al , 2009 communicati on is about to ta ke precedent over the traditional top down approach used by leaders to interact with employees. --Today's leaders achieve fa r more engageme nt and c redibility when they take part in genuine conversation with the people who work for and w ith them.…”
Section: Communicationmentioning
confidence: 99%